Heritage discontinued: tracing cultural ecologies within a context of urban transition - Sohie, Caroline (Department of Civil Engineering, 2017)
Culture has been consistently underrepresented in the sustainability debate and often perceived as a constraining factor to modern-day advancement. However in recent years, the broadening development paradigm in the Global South is increasingly asserting culture's indispensable role in sustainable human development. This dominant cultural paradigm mainstreamed by UNESCO is subscribed to by government and other role-players within the domain of culture and urban development. Despite its significant achievements, it however comes with a specific heritage conceptualisation, which is disconnected from local reality and perpetuates a problematic theoretical construct of cultural legacy, which is steeped in a Eurocentric conservation bias with colonial undertones. The thesis argues that this model will not lead to transformative interventions in urban areas that harness the power of culture if its interpretation remains decontextualised and perpetuates an instrumentalised view of culture and cultural conservation practice, inherited from the past. The thesis explores how an alternative conceptualisation of culture, based on the concept of cultural ecologies, can be more meaningful and beneficial in contributing to the theoretical reassessment of the human settlements imaginary. This is achieved through an interdisciplinary literature review and a case study of Bagamoyo, a small urban settlement in Tanzania. Through a systematic diagnosis of this small scale locality, cultural ecologies are foregrounded through the primary lens of the urban public-private interface and framed within a context that is shaped by the dynamics of globalisation. Additionally, the study takes place against the backdrop of a failed UNESCO World Heritage application, which allows me to discuss the undercurrents and invested interests associated with cultural heritage politics and the traumatic impact global conventions can have on local sustainability. It concludes in a proposed approach that repositions culture at the core of social exchange and argues that cultural sensitive development is an ongoing socio-cultural production process. Its potential lies in capturing the layered 'ordinariness' of place and in harnessing the imaginative responses arising from local idioms, practices and traditions as the shared imaginary of tomorrow.